Trigonometry plane and spherical - Salumbides, Epifanio N.; Romero, Rufo C. (Quezon City, Philippines : Royal Publishing House, Inc., 1963)
The justification for the adoption of a new book on trigonometry should not be based simply on its authorship by Filipino writers. The new textbook must have other qualities if it is to avoid being recognized as an imposition in the classroom. One of the requisites for an acceptable textbook is that it must be expressed in language which is readily understood by its reader.
Chapter 1. Measurement of angles -- Chapter 2. Trigonometric functions of an acute angle -- Chapter 3. The right triangle -- Chapter 4. Logarithms -- Chapter 5.Obtuse angles -- Chapter 6. Functions of one angle -- Chapter 7. Functions of two or more angles -- Chapter 8. Oblique triangles -- Chapter 9. Inverse or circular trigonometric functions -- Chapter 10. Complex numbers -- Chapter 11. Review solid geometry -- Chapter 12. General Laws -- Chapter 13. The right spherical triangle -- Chapter 14. Oblique spherical triangles -- Chapter 15. Application of spherical trigonometry.
Includes bibliographical references.
Keywords: TRIGONOMETRY -- SPHERICAL -- PLANE